Cytokines and Chemokines in Neuromyelitis Optica: Pathogenetic and Therapeutic Implications - Uzawa, Akiyuki (Brain Pathol, 2013)
Neuromyelitis optica (NMO) is characterized by severe optic neuritis and longitudinally extensive transverse myelitis. The discovery of an NMO‐specific autoantibody to the aquaporin‐4 (AQP4) water channel has improved knowledge of NMO pathogenesis. Many studies have focused on inflammatory and pathological biomarkers of NMO, including cytokines and chemokines. Increased concentrations of T helper (Th)17‐ and Th2‐related cytokines and chemokines may be essential factors for developing NMO inflammatory lesions. For example, interleukin‐6 could play important roles in NMO pathogenesis, as it is involved in the survival of plasmablasts that produce anti‐AQP4 antibody in peripheral circulation and in the enhancement of inflammation in the central nervous system. Therefore, assessment of these useful biomarkers may become a supportive criterion for diagnosing NMO. Significant advances in the understanding of NMO pathogenesis will lead to the development of novel treatment strategies. This review focuses on the current advances in NMO immunological research, particularly that of cytokines and chemokines.